L’union franco-tupi dans l’expérience mystique de la France Equinoxiale - Andrea Daher (Nuevo mundo - Mundos Nuevos, 2018)
This text highlights the potentialities of rhetorical analysis to reflect on governance representations and practices in early modern period. Based on a corpus of accounts by Capuchin friars Claude d'Abbeville and Yves d’Évreux, missionaries sent to the Brazilian colony, France Équinoxiale, in the first decades of the 17th century, this study shows how literate practices were structured by "representation" as a cultural form of Catholic politics, carried out by rhetorical inventio that unified metaphysics, theology, ethics and politics. These discourses allow us to put into question how was built, in the discourse pragmatics, the ethical-theological-political point of view on the Indians and how were mobilized the rhetorical commonplaces of the mystical Franco-tupi union. Conceived from the organization of the collective body of the Brazilian colony, this mystical union brought together individual wills in the unique and legitimate will of the French Christian state. Thus, France Équinoxiale colony realized the vocation assumed by the Capuchin mission as a ‘mirror’ of the French Catholic monarchy, where the regularity of the law on indigenous custom is established, and the Franco-Tupi friendship is then embodied within the ‘common weal’ of nations.